Ethnochemistry: Analysis the Relevance of Elements Periodic System in the Making of Kawali Bugis Bone as a Learning Chemistry Source - Yusaerah, Nur; Imranah, Imranah; Sartika, Sartika; Fajrah, Nur (Universitas Pendidikan Mandalika, 2024)
Kawali is one of the war tools of the Bugis Bone community which in its manufacture involves the process of forging, carving, chiseling, and the use of artistic symbols which are used as cultural heritage. Given the importance of knowledge about the benefits of chemistry in life, knowledge about the chemical elements contained in the kawali cultural heritage is needed as an effort to foster learning awareness that is integrated with local wisdom values. This research was carried out to reveal the fundamental chemical activities contained in the kawali making process starting from the forging and folding process, blade formation, ornament formation and electroplating which can be used as a source of learning chemistry by paying attention to the chemical concept involving chemical elements in the kawali making process. This research adopts a qualitative descriptive approach with ethnographic methods, involving observation, interviews, and documentation. The data analysis process is carried out inductively using source triangulation, so that key, primary, and supporting informants are selected for each aspect that is the focus of the study. The results of the research show that the fundamental activities in the process of making kawali Bugis Bone include heating and expansion, metal extrusion, metal reduction and electroplating with chemical concepts including metal elements, electron configuration, metal properties, corrosion, redox reactions, and metal alloys, as well as chemical elements involved in the manufacturing process, namely iron, steel containing carbon, manganese, silicon, aluminum, nickel, chromium, cobalt, molybdenum and vanadium.